La institucionalización nacional como estrategia para enfrentar los cambios sociales por la globalización y la sostenibilidad del modelo económico - Barrera Herrera, Jorge (2010)
It is undeniable that the globalization trend is irreversible. Today, access to economic development is unthinkable without being able to participate in global trade, especially trade with all countries and in all fields is possible and desirable. In this paper, we analyzes and propose some answers about the demand of 30% of the electorate in the recent Peruvian presidential elections who called for a “radical change”, despite substantial and sustained economic growth in the 10 years, with unprecedent progress in reducing poverty but modest reduction in income inequality. The analysis is reviewed within a general framework for globalization in which Peru is actively involved and we see the importance in this process of trade and integration in the market, consumption and credit. It is stressed the effect of the current “unregulated” global monetary system which encourages global imbalances, generating new structural trends in society and their implications for our society in particular. We conclude that, given the persistent problems of wealth redistribution that creates dissatisfaction of citizens, to achieve democratic stability and continuity of the economic model it is necessary to improve deliberative spaces and empower citizens, especially the poorest ones, in the model of growth in globalization, highlighting as a key strategy the national institutionalization process for the construction of a project country.